The Effect Of Wheatly Strategy In Collection And Development Of The Direction Towards The Arab Line For Art Education Student - Abbood Al dulaimy, Atia Wassa; Ali Hassan, Firas; Sobeih Mahmoud, Mohamed (Opción, 2019)
Arabic calligraphy and Islamic decoration are a civilized identity for the Arab countries of the world and their historical importance is taught in the colleges of Iraqi universities, and as an attempt by researchers to confirm the importance of interest in it, a strategy was applied according to the Wheatley model to develop students’ attitudes and to increase their educational attain- ment in it, the researchers identified the problem of their research with the following question: What has the effect of a strategy It is followed in collect- ing and developing the trend towards Arabic calligraphy for Iraqi students at Al-Mustansiriya University / College of Basic Education - Department of Art Education? The researchers applied the experiment during the second semes- ter of the academic year 2018-2019 at (3) hours per week. They concluded that the use of Wheatley’s strategy leads to the development of students’ attitudes towards Arabic calligraphy and its use and works to raise the educational attainment level for students of the second stage of the Department of Art Ed- ucation in the Arabic Calligraphy subject, therefore researchers recommend the use of Wheatley’s strategy in teaching, especially in the Department of Art Education at the College of Basic Education for its positive impact and so that it is possible Benefiting from the current study in implementing activities and skills of Arabic calligraphy